STEAM in the Frame of Independent Curriculum in Elementary School - Rizki Putri Wardani; Chumi Zahroul Fitriyah; Annur Rofiq; Wiwin Hartanto; Vit Ardhyantama (STEAM Journal For Elementary School Education, 2025)
The independent curriculum is a curriculum that was implemented in Indonesia in 2021 until now. Various approaches are implemented in the curriculum, one of which is STEAM. The purpose of writing this article is to identify and analyze the STEAM approach in elementary school learning that is aligned with the principles of the Merdeka Curriculum, and provide recommendations for developing contextual and integrative learning that supports the achievement of the Pancasila learner profile and 4C skills, student activities, and learning outcomes. The research method used is a literature study by reviewing journals as literature recorded in Sinta, Garuda, and indexed nationally and internationally. The results showed that there are many learning models that integrate with the STEAM approach in the independent curriculum which effectively provide results in increasing the achievement of the Pancasila learner profile, 4C skills, student activity, and learning outcomes. This STEAM approach encourages students to be active in various learning activities designed by teachers in the independent curriculum and gain direct experience both theoretically and practically.